KEBERHASILAN PEMIJAHAN SEMI ALAMI IKAN SEPAT MUTIARA (Trichogaster leeri Blkr) DALAM MEMPRODUKSI BENIH - Sukendi Sukendi; Ridwan Manda Putra; Yurisman Yurisman (Fakultas Perikanan dan Kelautan, Universitas Riau, 2012)
This Research aims to determine the success of the semi-natural spawningin mosaic gouramy (Trichogaster leeri Blkr) by giving different substrates on thecontainer spawning. a pair of mosaic gouramy that have matured gonadscombined at the aquarium spawning that has been equiped with running watersystems. Treatments given were different substrates at the aquarium, P1 = thewater hyacinth substrate, P2 = hydrilla substrate, P3 = the smoothed rafia ropesubstrate. Each treatment carried out repeated three times to obtain 9 units trial.Parameters measured were spawning time, amount of eggs spawned, the value offertilization and egg hatchability values. The results showed that the besttreatment is the treatment P2 (hydrilla substrate) produces the shortest duringspawning time 49.33 hours, amount of eggs spawned 195 eggs, fertility value of71.93% and 60.09% egg hatchability.Keywords: Trichogaster leeri, spawning time, amount of eggs spawned, valueof fertilization and egg hatchability values